Analysis of the electrical and optical properties of PEDOT:PSS/PVA blends for low-cost and high-performance organic electronic and optoelectronic devices. (21st April 2015) - Carr, Olivia; Gozzi, Giovani; Santos, Lucas Fugikawa; Faria, Roberto Mendonça; Chinaglia, Dante Luis
Abstract: In this study we propose the use of a blend, comprising poly(3, 4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) and polyvinyl alcohol (PVA), to be used as flexible, semitransparent and highly conductive material for electronic and optoelectronic devices. The electrical conductivity and optical transmittance of spray-deposited films of the blend, in different thicknesses and at different weight ratios, were studied in order to determine the most appropriate composition for optimal device performance and cost. We propose a direct method to determine the most appropriate blend composition to produce polymeric films with a desired sheet resistance, optical transmittance and cost, by using a diagram which considers the influence of blend composition and film thickness in a light-transmittance versus sheet resistance plot, mediated by the material cost per unit area. In this way, the present study establishes an empirical method to determine the PEDOT:PSS/PVA blend composition to be used as electrode material in optoelectronic devices which satisfies the desired conditions of optical transmittance, sheet resistance and cost-effectiveness.